Etiology and Outcome of Acute Hepatic Failure - A Study of 40 Cases - Islam, N; Abdullah, ABM; Zaman, A (Bangladesh Medical Journal, 2009)
Acute hepatic failure (ALF) is a medical emergency and infrequently presented in the hospitals and may be associated with high mortality rate. Its etiology shows considerable geographical variations. The viral causes are the most common worldwide, [whilst acetaminophen (Paracetamol) induced hepatotoxicity forms the most common precipitant in many developed countries.] A total forty (40) patients of ALF were studied during the period of January 2003 to July 2004 to evaluate the etiology and outcome. The patients were admitted in different tertiary care hospitals in Bangladesh. The patients were selected randomly by the diagnostic criteria. The selected patients presented with jaundice and hepatic encephalopathy of varying grades. Almost all the cases the causative agents were viruses. Among these, the hepatitis E virus (HEV) was the top most causative agent followed by hepatitis B virus (HBV) in this study. Despite good effort of conservative treatment, the mortality rate was 77.5%. The mortality rate was higher in grade-III and grade-IV encephalopathy patients whereas the prognosis is better in grade-I and grade-II encephalopathy patients. DOI: 10.3329/bmj.v38i2.3575 Bangladesh Medical Journal 38(2) 2009 56-59